The Influence of Sociocultural Practices of Society on Health: The Influence of Sociocultural Practices of Society on Health - Ratnasari, Dewi (International Journal of Health, Medicine, and Sports, 2023)
The influence of people's sociocultural practices on health has been a major focus in global health studies. In an era of rapid change, recognition of the complex impact of cultural practices, values, and traditions on physical and mental well-being is increasingly important. Health today is thought to be the result of interactions involving biological, social, environmental, and psychological factors. The study collected and analyzed literature, qualitative approaches, and field data to investigate the influence of sociocultural practices on health. The study's findings point to several key aspects in this context. Diet and physical activity have a significant role in sociocultural influences on health. People's diets that reflect cultural values and the availability of natural resources can contribute to chronic disease risk. Physical activity, which is also influenced by social and cultural factors, has an impact on overall health. Traditional medicine also has a great influence on health. Some communities still rely on hereditary medical practices, which can often complement modern medical care. Social support also has an impact on mental and physical health, with strong support networks playing a role in reducing stress and improving well-being. In addition, perceptions of disease and spiritual factors also play a role in sociocultural practices that affect health. Some communities may associate illness with spiritual aspects, while others are more likely to see it as a result of biological factors. In conclusion, the sociocultural practices of society have a strong influence on the health of individuals and communities. Diet, traditional medicine practices, social support, and perceptions of disease are all interrelated and form complex interactions. A deeper understanding of these factors is important in developing a holistic and sustainable health approach that considers cultural and social diversity. Collaboration between health professionals, social scientists, and the public is needed to optimize the positive impact and reduce the negative impact of sociocultural practices on health.